Diagnosis of fungal keratitis caused by Nectria haematococca through next-generation sequencing: review of literature and report of three cases. (June 2023) - Wang, Wei; Luo, Ban; Yuan, Xu; Xu, Lingjuan; Gao, Jing; Liu, Shiliang; Den, Chaohua; Tan, Yongyao; Su, Guanyu; Chen, Zhongju; Zhang, Hong; Zheng, Zhifen; et al.
Highlights: It is the first clinical report of Nectria haematococca infection in humans. N. haematococca keratitis is severe and likely to recur after keratoplasty. The recurrence occurred primarily in the second week after keratoplasty. The effect of local use of fluconazole and voriconazole is not ideal. The next-generation sequencing is useful in the diagnosis of rare fungal infections. Abstract: Objectives: Fungal keratitis (FK) is a kind of serious corneal infection and penetrating keratoplasty (PKP) is needed when medical therapy fails. Although Nectria haematococca is found as endophytes in the roots of some plant species, there has been no report of N. haematococca infection in human. Methods: We reviewed 46 patients who underwent PKP due to FK in our hospital from July 2021 to December 2021, and there were three patients who had relapsed. The next-generation sequencing revealed that all three corneas were infected with N. haematococca . Results: Based on the ocular manifestation and treatment course of three cases, we summarize the characteristics of N. haematococca FK: the scope of corneal infection was widespread with severe hypopyon. The effect of local use of fluconazole and voriconazole was not ideal, and PKP was the main treatment. Even after a large-scale corneal lesion resection, the lesion may recur. The recurrence occurred primarily in the second week after PKP. Conclusion: This is the first clinical report of N. haematococca infection in humans. Compared with the other currently known FK caused by the Fusarium solani species complex, N. haematococca keratitis is more severe and more likely to recur.